Two New Threatened Species of Psyllocarpus (Rubiaceae; Spermacoceae) from Eastern Brazil - Martins Do Carmo, Joao Afonso (2018)
Two new species of Psyllocarpus sect. Psyllocarpus are here described and illustrated. Psyllocarpus bahiensis and Psyllocarpus scatignae, from the campo rupestre s. l. of Bahia and Minas Gerais states, respectively. We provide comments on their distribution, habitat, conservation status, and taxonomy. In addition, we analysed floral, fruit, and seed micromorphology, aswell as pollen grains of the new species. We also provide an updated identification key to the species of P. sect. Psyllocarpus.